PERIOPERATIVE MEDICINE - A NEW FIELD OF SEVERE BURN INJURY TREATMENT - Sorokina, O.Yu.; Filip, Zh.V.; Buryak, T.O.; Shepitko, K.V. (World of Medicine and Biology, 2018)
The study includes the results of perioperative examination and treatment of 75 surgical patients with burns. It was determined that the terms of severe burns surgical treatment (ST)are influenced by the presence of comorbidity, flame burn (93.3%) with simultaneous respiratory tract injuries (53.3%). It was established that a complicated course of the burn disease (BD)was associated with an increase of a deep burn area > 20% (p = 0.001), the volume of infusion therapy on the 1st day (р=0.001) and on the 2nd day (р=0.005) of the burn shock with the need to increase the rate of intravenous crystalloids administration to achieve the target diuresis rate of > 0.5 ml / kg / h during the first 24 hours after the burn (p = 0.001). The expediency of observing the tactics of “Damage Control Resuscitation”, which is aimed at performing surgical treatment of burns, taking into account the stabilization of the patient’s condition and the possibility of the body’s adaptive capabilities, is substantiated. This necessitated the development and use of a perioperative management scheme for patients, which contributes to the restoration of homeostasis indices against the background of staged surgical interventions with severe burns.
Keywords: burn disease; intensive care; metabolic response; systemic inflammatory response syndrome; perioperative medicine